ETHANOL PRODUCTION FROM TUBER GANYONG (Canna Edulis Kerr.) BY Saccharomyces cerevisiae WITH THE ADDITION OF Spirulina Sp. - Sukanadi, I Putu; Kartika, Rudi; Hindryawati, Noor (Jurusan Kimia FMIPA UNMUL, 2017)
This study demonstates the potential of starch tuber ganyong (Canna edulis Kerr.) as a substance for making ethanol by Saccharomyces cerevisiae with microalgae addition of Spirulina sp. as a source of nutrients in the fermentation process of ethanol has been carried out. The study also aims to determine the amount of nutrient concentration and fermentation time was used to generate the optimum ethanol content. Hydrolysis process by enzymatic is done through a liquification phase with α-amylase and saccharification phase with gluko-amylase. Furthermore the process of fermentation stage with the variation of the time (132 hours, 156 hours, 180 hours and 204 hours) using the yeast Saccharomyces cerevisiae with the addition of Spirulina sp. as a nutrient in the variation of Spirulina sp. concentrations (0,6 % (w/v), 1,2 % (w/v) and 1,8 % (w/v)). The result showed the sugar reducing after of hydrolysis was obtained with amount of 0,527 %, increased from the initial state with amount of 0,351 %. The highest ethanol content be found on the increase nutrient with amount of 1,2 % (w/v) by is time of fermentation to180 hours.